TEACHER TRAINING FACULTIES FROM RETROSPECTIVE TO PERSPECTIVE - Vasilijević, Danijela (Metodička teorija i praksa, 2026)
Emphasizing the importance of the quality of teacher education from the perspective of projecting social and educational realities, questions regarding the academic education of teachers in Serbia have been considered – from the establishment of the first faculties for teacher education to the present day. The key objective of the research is to examine the enrollment potential of state teacher training faculties in the past (from 1993/94 to 1997/98) and now (from 2019/20 to 2023/24) with the intention of projecting the current state. The research, of a transversal nature, was conducted using descriptive methods. By comparing quantitative indicators, the interest and quality of candidates for enrollment in teacher (pedagogical) faculties in central and western Serbia over the first and last five years of operation were analyzed, excluding the non-standard academic year 2025. The research sample is intentional and consists of ranking lists of teacher (pedagogical) faculties from Užice and Jagodina. The findings showed a serious tendency of decreasing interest in enrolling in teacher studies; a dominance of candidates with very good academic performance, with a noted decrease in interest from excellent students in the teaching profession by one-third in the last period. The affirmation of the teaching profession in Serbia should be considered a priority national issue.
Keywords: education; teaching; teacher; candidate selection